SecLEACH – A Random Key Distribution Solution for Securing Clustered Sensor Networks - Oliveira, Leonardo B.; Wong, Hao Chi; Bern, Marshall; Habib, Eduardo; Loureiro, Antonio A. F.; Dahab, Ricardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2005: Anais do V Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2005.21529, 2005)
Wireless sensor networks are ad hoc networks comprised mainly of small sensor nodes with limited resources, and can be used to monitor areas of interest. Recent work has shown that clustered sensor networks can increase system throughput, decrease system delay, and save energy. In this paper, we show that random key predistribution, first proposed and studied in the context of flat wireless sensor networks, is a very attractive key distribution solution for clustered sensor networks with rotating cluster heads, such as LEACH.